Composite PD and Fuzzy Logic Approach for Vibration of Elastic Joint Manipulator - Mohd Ashraf, Ahmad; Raja Mohd Taufika, Raja Ismail (2010)
The increased complexity of the dynamics of robots manipulator considering joint elasticity makes conventional model-based control strategies complex and difficult to synthesize. This paper presents investigations into the development of composite collocated proportional-derivative (PD) and Fuzzy Logic Control for trajectory tracking and vibration control of a flexible joint manipulator respectively. To study the effectiveness of the controllers, a collocated PD Controller is developed for tip angular position control of a flexible joint manipulator. This is then extended to incorporate a non-collocated Fuzzy Logic Controller for vibration reduction of the flexible joint system. Simulation results of the response of the flexible joint manipulator with the controllers are presented in time and frequency domains. The performances of the composite control schemes are examined in terms of input tracking capability, level of vibration reduction and time response specifications. Finally, a comparative assessment of the control techniques is presented and discussed.